Case reports about an overlooked cause of neck pain: calcific tendinitis of the longus colli. Issue 46 (November 2017) - Kim, Yeong-Jin; Park, Jae-Young; Choi, Ki-Young; Moon, Bong-Ju; Lee, Jung-Kil
Abstract: Study Design: Case description. Objective: Acute calcific tendinitis of the longus colli muscle is a rare clinical entity that causes severe neck pain. This entity is not well recognized due to its nonspecific presentation such as acute neck pain, neck stiffness, and odynophagia. The importance of this disease with a review of the literature is presented. Summary of background data: Acute calcific tendinitis of the longus colli muscle is an inflammatory condition caused by deposition of calcium hydroxyapatite in the superior oblique tendon fibers of the longus colli muscle. It can be misdiagnosed as other life-threatening conditions including retropharyngeal abscess, resulting in unnecessary medical or surgical interventions. Methods: We retrospectively reviewed the clinical data, radiological features, and laboratory reports of 8 patients who were diagnosed with acute calcific tendinitis of the longus colli muscle and seen at our institution between April 2008 and March 2015 in this article. We describe the clinical presentation, diagnosis, and treatment of acute calcific tendinitis of the longus colli muscle. Results: There were 5 men and 3 women who ranged in age from 41 to 49 years (mean age: 44.5 years). The associated symptoms included neck pain, stiffness, odynophagia, and headache. The duration of symptoms varied from 2 days to 1 week. All patients showed calcific deposition inferior to the anterior arch of the atlas, and prevertebral effusion extending from C1 to C4. All patients were treated with NSAIDs and immobilization with a cervical brace, and most patients showed complete resolution of symptoms within 1 week. Conclusion: We report 8 cases of acute calcific tendinitis of the longus colli, and describe the symptoms and radiological findings in detail. Awareness of this rare, benign, and self-limiting disease entity with characteristic radiologic findings is essential for early diagnosis and to avoid unnecessary medical and surgical interventions.